Access to Routinely Collected Clinical Data for Research: A Process Implemented at an Academic Medical Center - Susan C. Guerrero; Sujatha Sridhar; Cynthia Edmonds; Christina F. Solis; Jiajie Zhang; David D. McPherson; Elmer V. Bernstam (Wiley, 2019)
Electronic health records are valuable for clinical and translational research. Institutions must protect patient privacy and comply with applicable regulations while allowing appropriate access to clinical data for research. The processes that investigators must follow to access clinical data can be substantially different at different institutions. In this paper, we describe the process developed at our institution that has been active for 5 years and was used to satisfy over 200 requests for access to identified clinical data, usually within 1 day for internal requests and 3 days for visiting researchers.